2014
DOI: 10.1177/1556264614557238
|View full text |Cite
|
Sign up to set email alerts
|

A Learning Activity to Introduce Undergraduate Students to Bioethics in Human Clinical Research

Abstract: We developed a pharmacology practicum assignment to introduce students to the research ethics and steps involved in a clinical trial. The assignment included literature review, critical analysis of bioethical situations, writing a study protocol and presenting it before a simulated ethics committee, a practice interview with a faculty member to obtain informed consent, and a student reflective assessment and self-evaluation. Students were assessed at various steps in the practicum; the learning efficiency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…The data demonstrate that a modified IRB protocol experience within a CURE is associated with increased understanding of the three BREPs and how to apply them to everyday-life experiences. This result is consistent with previous findings showing that such experiences were associated with greater appreciation of ethical research principles (Kallgren & Tauber, 1996) and issues of informed consent and participant risks (Segarra & Gomez, 2014). The current investigation demonstrated that a mentored IRB-like activity was related to increased knowledge of ethical research issues as proposed by Hubbard and Ritchie (1995) as well as Olszewski (2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The data demonstrate that a modified IRB protocol experience within a CURE is associated with increased understanding of the three BREPs and how to apply them to everyday-life experiences. This result is consistent with previous findings showing that such experiences were associated with greater appreciation of ethical research principles (Kallgren & Tauber, 1996) and issues of informed consent and participant risks (Segarra & Gomez, 2014). The current investigation demonstrated that a mentored IRB-like activity was related to increased knowledge of ethical research issues as proposed by Hubbard and Ritchie (1995) as well as Olszewski (2019).…”
Section: Discussionsupporting
confidence: 92%
“…Increasingly, undergraduate research is being highlighted as an important opportunity for learning through an HIP (Kuh, 2008) by engaging students in faculty-led research and encouraging students to develop their own research projects in independent studies and senior capstone projects. This HIP can also involve introducing research into existing course instruction through course-based undergraduate research experiences (CUREs; Brownell & Kloser, 2015;Corwin, Graham, & Dolan, 2015;Segarra & Gomez, 2014;Teixeira-Poit, Cameron, & Schulman, 2011). Research on undergraduate research and CUREs has shown that students benefit from this mentored experience through increased knowledge and skill acquisition (Adedokun et al, 2014;John & Creighton, 2011;Stanford, Rocheleau, Smith, & Mohan, 2017), feelings of achievement in project ownership and selfefficacy (Adedokun et al, 2014;John & Creighton, 2011;Sandquist, Cervato, & Ogilvie, 2019), higher retention and graduation rates (Stanford et al, 2017), and greater commitment to the profession (Adedokun et al, 2014 ;Helm, & Bailey, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33 This is consistent with the outlook in professional decision making and validated in preliminary studies. 24 The initial theoretical reflection on moral concepts and the coherence with which the dilemmas are raised in both General Anthropology and Ethics-Bioethics facilitates critical evaluation of the ethical questions in a larger perspective. 34…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…23 These cases offer the students real-like situations and scenarios in routine practice and require reflection and implementation of the most basic professional qualities, fundamentally prudence. 13,24…”
Section: Description Of the Curriculummentioning
confidence: 99%